Phenobarbital: A New and Effective Corrosion Inhibitor for Mild Steel in 1 M HCl Solution - Singh, Ambrish; Pramanik, Tanay; Kumar, Ashish; Gupta, Monika (Asian Journal of Chemistry, 2013)
Phenobarbital was investigated as corrosion inhibitor for mild steel in 1 M HCl solution by weight loss and quantum chemical calculations. Phenobarbital showed 95 % inhibition efficiency at concentration of 200 ppm. The adsorption of the inhibitor followed Langmuir adsorption isotherm. The quantum chemical calculations were applied to elucidate adsorption pattern of inhibitor molecules on steel surface.